The rise of contractual publics - Splichal, Slavko (Javnost (Ljubljana), 2024)
The paper examines modern re-conceptualisations and re-contextualisations of publicness, proposing theoretical and empirical advancements in its conceptualisation. It critically analyses two significant developments following the English translation of Habermas’s seminal work, “Strukturwandel der Öffentlichkeit.” On the one hand, the book (re)affirmed the key role of communication and media in democratic politics and instigated a broad acceptance of the public sphere as a fundamental concept in academic discourse, leading to renewed research efforts and innovative developments. However, the subsequent conceptual fragmentation of (the concept of) the public sphere raised concerns about the loss of its original critical epistemic value. On the other hand, Habermas’s book obscured important sociological traditions, contributing to a divide between normative theory and sociological analysis, exemplified by a neglect of the habitual roots of public opinion and contractual bonds in the evolution of publics. These aspects gain relevance within the context of the platform economy and artificial intelligence governing internet communication. The paper concludes by introducing the concept of the contractual public, which draws on the evolving dynamics between public and private spheres, and proposing four strategies to revitalise publicness.
Keywords: communification; contractual public; counterpublic; Javnost; opportunity algorithms; public sphere; publicness